2020
DOI: 10.1038/s41598-020-78439-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of the antimicrobial compound tetrabromopyrrole and the Pseudomonas quinolone system precursor, 2-heptyl-4-quinolone, by a novel marine species Pseudoalteromonas galatheae sp. nov.

Abstract: Novel antimicrobials are urgently needed due to the rapid spread of antibiotic resistant bacteria. In a genome-wide analysis of Pseudoalteromonas strains, one strain (S4498) was noticed due to its potent antibiotic activity. It did not produce the yellow antimicrobial pigment bromoalterochromide, which was produced by several related type strains with which it shared less than 95% average nucleotide identity. Also, it produced a sweet-smelling volatile not observed from other strains. Mining the genome of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Fortimicin is an aminoglycoside antibiotic [ 31 ]. 2-Heptyl-4-quinolone is a kind of tetrabromopyrrole, which has been shown to exhibit antibiotic activity against human and marine bacteria [ 32 ]. Protomycinolide IV and rimocidine are macrolide antibiotics [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fortimicin is an aminoglycoside antibiotic [ 31 ]. 2-Heptyl-4-quinolone is a kind of tetrabromopyrrole, which has been shown to exhibit antibiotic activity against human and marine bacteria [ 32 ]. Protomycinolide IV and rimocidine are macrolide antibiotics [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PQS system has mostly been studied in clinical Pseudomonas strains, where it regulates virulence factors (such as biofilm, elastase, rhamnolipid or pyocyanin) production and promotes infection (as reviewed in García-Reyes et al, 2020). However, the synthesis of PQS and HHQ has been discovered in other genera, such as Burkholderia and a marine Pseudoalteromonas bacterium (Vial et al, 2008;Paulsen et al, 2020). In addition, it has been shown that PQS acts as a signal molecule in several Gram-negative and Gram-positive strains (including marine isolates) (Reen et al, 2011) as well as in multispecies marine communities (Wang et al, 2020), highlighting its role as a possible interspecies signal.…”
Section: Quorum Sensing and Quorum Quenching Pathwaysmentioning
confidence: 99%
“…Green algae are apparently less sensitive to AQs, as was shown by Patidar et al, who found that the inhibitory effects of AQs produced by Pelagibaca bermudensis were outweighed by other growth promoting effects when co-cultured with the green alga Tetraselmis striata [ 51 ]. Other AQs have been isolated from a variety of marine environments, including several unusual AQs from sponge-associated bacteria [ 52 , 53 , 54 ] and heptyl-quinolone from planktonic and algae-associated bacteria [ 27 , 55 , 56 ].…”
Section: Direct Effects Of Quorum-sensing Signals On Microalgal Growth and Metabolismmentioning
confidence: 99%